COMMUNICATION STRATEGY OF GLOBAL RADIO JAKARTA ANNOUNCERS IN MAINTAINING THE BROADCAST PROGRAM 'GOOD AFTERNOON SHOW' - Nashoha, Danu Rama; Nurmala, Nurmala (KOMUNIKOLOGI: Jurnal Ilmiah Ilmu Komunikasi, 2026)
This study aims to analyze the communication strategies of broadcasters at Global Radio Jakarta in maintaining the Good Afternoon Show program amid competition between radio stations. The study uses a qualitative approach with a descriptive method. Data were obtained through interviews with broadcasters as key informants, as well as division heads, producers, and production teams as supporting informants. The research analysis uses Larson's communication strategy model theory, which includes message selection, media determination, timing, audience approach, and evaluation of communication impact. The results of the study show that communication strategies are carried out through delivering light and communicative messages, utilizing radio as the main medium supported by social media, and evaluating based on listener feedback. These strategies play a role in maintaining audience loyalty and sustaining the existence of the Good Afternoon Show program.